2008
DOI: 10.1007/s10874-009-9127-4
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol characteristics during winter fog at Agra, North India

Abstract: Simultaneous measurements on physical, chemical and optical properties of aerosols over a tropical semi-arid location, Agra in north India, were undertaken during December 2004. The average concentration of total suspended particulates (TSP) increased by about 1.4 times during intense foggy/hazy days. Concentrations of SO 4 2− , NO 3 − , NH 4 + and Black Carbon (BC) aerosols increased by 4, 2, 3.5 and 1.7 times, respectively during that period. Aerosols were acidic during intense foggy/hazy days but the fog wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 40 publications
(63 reference statements)
1
22
1
Order By: Relevance
“…Chemical characterization of aerosols, their mass size distribution studies and its variation in different seasons at Dayalbagh, Agra has also been reported by Kumar et al (2007). Earlier study by Safai et al (2008) at Agra reported chemical characterization of aerosols only during a specific land campaign (December 2004) for intense foggy or hazy days. In this paper, a systematic study of chemical characterization of water soluble fraction of TSP matter has been presented with data from two consecutive years (2009)(2010) and seasonal variation has also been discussed.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Chemical characterization of aerosols, their mass size distribution studies and its variation in different seasons at Dayalbagh, Agra has also been reported by Kumar et al (2007). Earlier study by Safai et al (2008) at Agra reported chemical characterization of aerosols only during a specific land campaign (December 2004) for intense foggy or hazy days. In this paper, a systematic study of chemical characterization of water soluble fraction of TSP matter has been presented with data from two consecutive years (2009)(2010) and seasonal variation has also been discussed.…”
Section: Introductionmentioning
confidence: 66%
“…Several researchers have attempted to study the chemical composition and mass size distribution of atmospheric aerosols at different places (Shrestha et al, 2000;Wu et al, 2006;Pio et al, 2008;Stone et al, 2011;Hu et al, 2012;Tsai et al, 2012). In India also, studies on chemical characterization and mass size distribution of water soluble ionic constituents in aerosols have been conducted (Khemani et al, 1985;Safai et al, 1993;Tripathi et al, 1996;Kumar et al, 2003;Rastogi and Sarin, 2005;Kumar et al, 2006;Safai et al, 2008;Kulshrestha et al, 2009;Safai et al, 2010;Deshmukh et al, 2011;George et al, 2011;Ram et al, 2012). Few studies have been carried out in the IndoGangetic plain to characterize TSP (Kulshrestha et al, 1998;Parmar et al, 2001;Kumar et al, 2007;Ram et al, 2010;Ram et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Aruna et al [32] found about two times higher nighttime value than daytime at Chennai. As per available literature, some cities also have high BC mass loading during nighttime: Dhanbad [31] and Agra [33].…”
Section: Daytime and Nighttime Averagesmentioning
confidence: 84%
“…Through the fog processing, OC, ECOC, V-ECOC and EC-Sulfate were generally enhanced with the secondary inorganic species (sulfate, nitrate and/or ammonium). The enhanced secondary inorganic species in aerosols were commonly observed throughout the foggy episodes (Biswas et al, 2008;Safai et al, 2008). However, the EC-fresh and Biomass particles were probably freshly emitted more during the episode, so there was no obvious variation of the secondary species in their mass spectra.…”
Section: Case Study Of Carbon-containing Particles Under Specific Metmentioning
confidence: 96%